'Grey' must come before 'green' in the farming revolution - Sene, Djibril (Technical Centre for Agricultural and Rural Cooperation, 1992)
Mr Djibril Sene, formerly Minister of Agriculture and of Research in Senegal, is currently President of the Foreign Affairs Commission of the Senegalese parliament. He plays a major part on the international stage in agricultural policy formulation....